Immunoaffinity isolation of CEACAM1 on hydrazide-derivatized cellulose with immobilized monoclonal anti-CEA antibody - Muchová, L; Jirsa, M; Kuroki, M; Dudková, L; Benes, M J; Marecek, Z; Smíd, F (Biomedical chromatography, 2001)
Carcinoembryonic cell adhesion molecule 1 (CEACAM1) is a human membrane glycoprotein belonging to the carcinoembryonic antigen (CEA) family and to the immunoglobulin superfamily. It is expressed in apical membranes of many epithelial cells in gastrointestinal and urogenital tract and also in granulocytes and lymphocytes, and its biological effect in human tissues has recently been discussed in literature. The purpose of this study was to isolate CEACAM1 glycoprotein from bile and characterize its purity and recovery which has not been described before. Affinity chromatography of CEACAM1 on hydrazide-activated cellulose with immobilized monoclonal anti-CEA F34-187 antibody is described. The immunoglobulin carbohydrate moiety was oxidized by periodate and then bound to hydrazide-activated matrix. Crude protein fraction from bile was applied on the affinity column and after extensive washing of non-bound proteins CEACAM1 was eluted with 6 M guanidine-HCl. A single immunopositive 85 kDa band was detected on Western blots with anti-CEA antibody after SDS-PAGE. We found out that CEACAM1 was not stainable with any common method of protein staining and the only non-specific method which could detect the 85 kDa band was a lectin staining.
Keywords: Electrophoresis, Polyacrylamide Gel; Antibodies, Monoclonal; Chromatography, Affinity; Hydrazines; monoklonální protilátky; Antigens, CD; hydraziny; celulosa; karcinoembryonální antigen; Carcinoembryonic Antigen; elektroforéza v polyakrylamidovém gelu; Cellulose; molekuly buněčné adheze; Cell Adhesion Molecules; chromatografie afinitní; Antigens, Differentiation; CD antigeny; diferenciační antigeny